Severe obstetric morbidity (near miss) - Vargas Hernández Víctor Manuel; Tovar Rodríguez José María; Becerril Rodríguez Paola Rocío (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2019)
Background: A case of "Near miss maternal" or severe obstetric condition is defined as the patient at risk of dying, which survives the complication that occurred during pregnancy, delivery or at the end of the puerperium; or women who have survived the risks that endanger their lives. Objective: To determine how many cases of severe obstetric morbidity and mortality were presented between January 2010 and December 2016, at the Hospital Juárez de México. Material and methods: A retrospective study was conducted, obtaining 130 cases with severe obstetric morbidity and 26 maternal deaths. The average mortality rate was 5.78% and death rate .415. The main causes of severe morbidity were obstetric hemorrhage, hypertension associated with pregnancy and sepsis.